Statement and explanation in the remembrance of the veterans of Abdullah al-Danushari - Abbas, Ahmed Mudheher (Journal of Tikrit University for Humanities, 2023)
This thesis is the economic gateway (al-Bayan and the two books in the remembrance of the veterans) by Imam Abdullah bin Abdul Rahman bin Ali in the year 1025 AH, and it consists of five plates, a unique copy. It did not reach us, so I wanted the short messages from the shelves of manuscripts to the publications from books and letters, so that the students of knowledge might benefit from them.